EFFECT OF EQUITY MARKET VALUE, LEVERAGE AND INFORMATION ASYMMETRY ON THE COST OF EQUITY CAPITAL IN LQ45 COMPANIES - Nadiah Sri Dewi; Harti Budi Yanti (EBID: Ekonomi Bisnis Digital, 2023)
This research was conducted to analyze the effect of Market Value on equity, Leverage, and Voluntary disclosure on the Cost of Equity Capital incorporated in LQ 45 companies on the Indonesia Stock Exchange. The data used in this research is secondary data, and a sample of 36 people is taken using purposive sampling technique. The data analysis method is multiple linear regression and the Classical Assumption test. The results of the analysis simultaneously show that the market value of equity, leverage and information asymmetry affect the cost of equity capital incorporated in LQ 45 companies on the Indonesia Stock Exchange. In part, the market value of equity affects the cost of equity capital incorporated in LQ 45 companies on the Indonesia Stock Exchange and voluntary disclosure is influenced by the cost of equity capital incorporated in LQ 45 companies on the Indonesia Stock Exchange.